Impact attenuation during gait wearing unstable vs traditional shoes - Pedro Pérez-Soriano; Roberto Sanchis-Sanchis; Juan F. Lison; Daniel Sánchez-Zuriaga; Salvador Llana-Belloch; Gemma Biviá-Roig; Pablo Salvador-Coloma (Asociación Española de Ciencias del Deporte, 2019)
Introduction: Impact force generates acceleration waves that travel through the body, and possible relationships may be exist between these acceleration waves and injuries. Several studies have analyzed the impact forces on the lower limb in healthy subjects wearing unstable shoes, but there is not accelerometric study analyzing the transmission of these impact forces along the locomotive system. The aim of the present study is to compare the acute effects of wearing unstable shoes (US) vs traditional shoes (TS), on maximum vertical acceleration, impact attenuation, cadence and stride length during gait. Methods: Fourty-three asymptomatic adults participated in the cross-sectional study. Subjects underwent gait analysis with simultaneously collecting heel and tibia peak acceleration, impact magnitude and acceleration rate, as well as shock attenuation and stride parameters (stride length, stride rate). Results: The results showed that wearing US increased cadence (10.99 steps/min; p<0.01), and decreased stride length (0.04 m; p<0.01). Additionally, an increase in maximum tibia peak acceleration, tibia impact magnitude and tibia acceleration rate were reported in the US condition compared to the TS condition, with a decrease of tibia attenuation in the US (p<0.05). Conclusion: Regarding shockwave transmission of ground reaction forces, a lower shock attenuation from the heel to the tibia was reported in the US vs TS condition. Bearing this in mind, it should be pointed that, while it is not yet clear if increased tibia acceleration is harmful to the musculoskeletal system, the US should be used with caution.